Why Has Europe Not Co-ordinated Its Fiscal Policies? - Boltho, A (1990)
Traditionally, economic policy cooperation in Europe has taken the form of setting common rules rather than taking discretionary action. This picture did not change in the 1980s. Despite high unemployment and decelerating inflation the EEC countries refrained from any coordinated expansionary fiscal policy. One reason for this may have been the surprisingly divergent views held by the policymakers of the four major economics on how such policies operated. While expansionary fiscal stances were universally condemned, the reasons given diverged widely. More important, however, than such intellectual confusion, was a common political determination to reduce public debts and public expenditure, diminish the role of the welfare state and restore the power of market forces.